Optimization of pesticide spray parameters and analysis of key physiological indicators for control efficiency against jujube leaf black spot - Zhang, Rui-Xia; Hao, Jun-Ya; Xiao, Ke; Liu, Ping (Frontiers in Plant Science, 2026)
IntroductionJujube leaf black spot is a common foliar disease in jujube orchards. Precision spraying technology enhances pesticide utilization efficiency through accurate targeting and on-demand application, while simultaneously mitigating environmental risks.MethodsIn this study, 1,000 jujube black spot leaves with different disease severity levels were selected, labeled, and photographed. Chemical treatments were applied at varying spraying distances and angles according to the disease severity, with a water control group established for comparison. The control efficiency of spraying parameters on jujube leaf black spot across different disease severity levels and their physiological effects on the leaves were measured.ResultsThe spraying parameters significantly influenced the control efficiency across different disease severity levels. For level 0 (prevention), a distance of 0.9 m and an angle of 0°; for level 1, a distance of 1.2 m and an angle of 0°; for level 2, a distance of 0.6 m and an angle of 40°; for level 3, a distance of 0.6 m and an angle of 20°; and for level 4, a distance of 0.9 m and an angle of 40°. The control efficiency showed a significant positive correlation with soluble sugar (SS) content and the activities of superoxide dismutase (SOD), peroxidase (POD) and phenylalanine ammonia-lyase (PAL). Among these, SOD and POD activities were identified as key physiological indicators for evaluating the physiological impact of chemical control on jujube leaf black spot across different severity levels.DiscussionBy investigating the graded control efficiency of spraying parameters on jujube leaf black spot, this study screened the optimal spraying parameters for graded disease control and identified key physiological indicators for evaluating control efficiency, providing a theoretical basis for the green control of jujube leaf black spot.